2017
DOI: 10.5935/1518-0557.20170003
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the number of embryos to transfer on day 5: two should be the limit

Abstract: ObjectiveTo define the appropriate number of embryos to be transferred at day 5.MethodsRetrospective analysis of 784 consecutive fresh day-5 embryo transfers performed between 2007 and 2015, divided in three groups: Group A (N = 219): received the only 2 embryos that reached a transferable stage; Group B (N = 357): received 2 selected embryos among several that reached a transferable stage; Group C (N = 208): received the only 3 developing embryos. Clinical pregnancy, implantation, multiple pregnancy and deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We also demonstrated that sequential single blastocyst transfer in women 40 years of age or older twice, as compared to a one-time double blastocyst transfer, results in a higher cumulative pregnancy rates [6]. Suggesting that endometrial dys-synchrony may be overcome in a subsequent cycle and confirming that the endometrium plays an important role in the probability of pregnancy at any given embryo transfer [6,[8][9][10][11]. In a randomized study comparing transferring a single euploid blastocyst after trophectoderm biopsy or two untested embryos, transferring two embryos resulted in similar pregnancy and ongoing pregnancy rates but much high rates of multiple gestation (54% vs. 0%) [12].…”
mentioning
confidence: 54%
“…We also demonstrated that sequential single blastocyst transfer in women 40 years of age or older twice, as compared to a one-time double blastocyst transfer, results in a higher cumulative pregnancy rates [6]. Suggesting that endometrial dys-synchrony may be overcome in a subsequent cycle and confirming that the endometrium plays an important role in the probability of pregnancy at any given embryo transfer [6,[8][9][10][11]. In a randomized study comparing transferring a single euploid blastocyst after trophectoderm biopsy or two untested embryos, transferring two embryos resulted in similar pregnancy and ongoing pregnancy rates but much high rates of multiple gestation (54% vs. 0%) [12].…”
mentioning
confidence: 54%